Patterns of Burns among Children up to Five Years Old in El-Minya - Egypt - GadAllah, Ahmed Mohmed (Journal of medical and pharmaceutical sciences, 2019)
Objective: The purpose of this study is to assess the patterns of burns and scalds among young children in El-Minya. Methods: 2 years prospective study of all burns involved children (ages, 0- 5years) presenting of five Emergency Departments in El-Minya governorate. Data extracted from the cases by reviewing the medical records of patients attending the emergency department-treated burns include age, gender, body part, causal substance, disposition, mechanism of the injury, and injury pattern. Results: A 2117 patients ≤5 years old were treated in El-Minya emergency departments and evaluated for burn-related injuries. Boys constituted 61.4% of scalds and 55.6% of thermal burns. 81.4% of injuries were scalds, 13.9% were contact burns, and 4.7% were burns from other causes. One-year-olds was at the highest risk for scalds and thermal burns. Hospitalizations was significantly increased among patients with scalds than did thermal burns. Hot water and soup were the chief causal agents for scalds 59%. The 2 most common scald injury patterns was among children reached up and pulled a pot of hot water and soup off the stove or other elevated surface 29.5% and children grabbed, overturned, or spilled a container of hot water and soup onto him- or herself 24.7%. Scalds affected the front of the body presented 93%. Predominantly to face, arms, and upper trunk. Contact burns caused by touching hot items presented 69.4% and injuries sustained more indoor formed 71.8%. Conclusion: Burns are common and generally severe in Upper Egypt among children 5 years old and younger. One – year – olds was at the highest risk for scalds and thermal burns who pulled or spilled hot water and soup over themselves and sustained burns from touching hot items as oven, pans, pots, motorcycle exhaust pipe, brazier, kettle, and iron, so one – year – olds are a high priority for targeted prevention. The duty to provide all children with safe surroundings in which to develop. Recommendation: Preventative strategies should be targeted at creating safe home environments through family education, financial support to poor family, legislation and engineering safer cooking and lighting means.